(untitled) (Journal of Health, Population and Nutrition, 2010)
Patent medicine vendors (PMVs) are a ubiquitous feature of the informal health sector in Nigeria. A previous study on healthcare-seeking behaviour of persons with chronic cough in southern Nigeria found that over 60% of respondents chose the PMV as a healthcare provider of first instance. This study sought to determine the willingness and capability of PMVs to play a role in the national tuberculosis (TB)-control effort. Study sites were selected through a multi-stage sampling process. In total, 388 PMVs, 17 principal officers of PMV associations, and 17 community leaders were purposively selected. Sets of structured questionnaire were administered to the PMVs while information from the principal officers of PMV associations and community leaders was elicited through in-depth interviews and focus-group discussions (FGDs). Quantitative data were collated using the Epi Info software (version 6.04) and analyzed using the SPSS software (version 15). Most (90%) PMVs indicated that they would be ready to cooperate with the national TB-control programme, if trained. Seventy-three percent attended persons with prolonged cough in the course of their career. However, 48% did not know the cause of TB. Only 3% ever-attended a training session on TB control. Sixty-six percent completed at least 12 years of schooling with secondary school certificate. Eighty percent of the community leaders were happy with the work of PMVs. About two-thirds (65.6%) of the PMVs were male. The PMVs are positively disposed to playing roles in TB control. Given this positive disposition and their widespread acceptance in healthcare-delivery in the communities, they have potentials for playing a role in TB control in southern Nigeria. Key words: Patent medicine vendor; Tuberculosis; Nigeria DOI: 10.3329/jhpn.v28i6.6605 J HEALTH POPUL NUTR 2010 Dec;28(6):567-577